2016
DOI: 10.1111/his.12855
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical p63 expression discriminates between primary cutaneous follicle centre cell and diffuse large B cell lymphoma‐leg type, and is of the TAp63 isoform

Abstract: Functional studies are required to clarify the significance of p63 overexpression in primary cutaneous B cell lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…P63 is positive in a significant amount of DLBCL cases, with percentages ranging from 15 to 70% depending upon the study examined [37]. The correlation between p63 expression and overall survival remains unclear; however, studies have shown a correlation of p63 with a high proliferative index, suggesting its involvement with DLBCL tumor progression [5, 6]. …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…P63 is positive in a significant amount of DLBCL cases, with percentages ranging from 15 to 70% depending upon the study examined [37]. The correlation between p63 expression and overall survival remains unclear; however, studies have shown a correlation of p63 with a high proliferative index, suggesting its involvement with DLBCL tumor progression [5, 6]. …”
Section: Discussionmentioning
confidence: 99%
“…These isoforms, among other functions, are responsible for the regulation and differentiation of stratified epithelial cells. Changes in isoform expression lead to proliferation and differentiation of these tissues and also play an active role in neoplasia [5, 8]. While p53 is widely acknowledged as a tumor suppressor gene and its mutations are responsible for tumor progression, the role of p63 as a cancer oncogene continues to be studied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations